2011
DOI: 10.1159/000327918
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Idiopathic Pulmonary Fibrosis: A Review

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive diffuse parenchymal disease with a poor prognosis. Pulmonary hypertension (PH) often complicates the course of IPF and may even be found in patients with preserved lung function. Possible pathogenetic mechanisms of PH in IPF include vascular destruction, pulmonary hypoxic vasoconstriction and vascular remodeling due to overexpression of cytokines and growth factors. PH in IPF patients is associated with decreased exercise capacity and a worse prognosis. Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 182 publications
(172 reference statements)
5
45
1
2
Order By: Relevance
“…The lungs of patients with IPF are marked with recurrent epithelial injury and remodeling, which can directly affect local blood-gas exchange and result in hypoxia (2,32,33). Our studies confirm previous observations that Hif-1a levels are elevated in experimental pulmonary fibrosis and in IPF (3), and demonstrate that Hif1a-mediated up-regulation of DCK in hyperblastic epithelial cells in the lungs is necessary for the development of extensive fibrosis.…”
Section: Discussionsupporting
confidence: 88%
“…The lungs of patients with IPF are marked with recurrent epithelial injury and remodeling, which can directly affect local blood-gas exchange and result in hypoxia (2,32,33). Our studies confirm previous observations that Hif-1a levels are elevated in experimental pulmonary fibrosis and in IPF (3), and demonstrate that Hif1a-mediated up-regulation of DCK in hyperblastic epithelial cells in the lungs is necessary for the development of extensive fibrosis.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the increased mortality due to PH, there are no effective clinical or molecular markers that can be used to predict or evaluate its development or progression (5,7,32,33). In line with this, we report no significant correlations between mPAP values and pulmonary function tests or blood gas values, a phenomenon that has been reported previously and has been ascribed to a lower sensitivity of these tests to detect ORIGINAL RESEARCH changes in pulmonary vascular tone (34).…”
Section: Discussionsupporting
confidence: 86%
“…In a recent study, KIMURA et al [32] confirmed by multivariate analysis that a high mean PAP value measured at the initial evaluation of IPF patients undergoing RHC is an independent predictor of survival. Unlike many other studies [1,33,34], this retrospective analysis focused on IPF patients affected by milder disease (mean FVC 70.2%, and mean DLCO 47.9%) [32]. The study demonstrated the importance of the initial evaluation of PH and supported previous observations indicating that PH is not just a result of restrictive impairment in patients with IPF [1,20,35].…”
Section: Prognostic Significance Of Ph In Ipfsupporting
confidence: 71%